Determination of the Rate of Litter Decomposition and Dynamic of Carbon, Nitrogen and Phosphorus of Fagus orientalis in Asalem and Vaz Regions - HOSSEINI, VAHID; AZIZI, PIROUZ (Asian Journal of Chemistry, 2010)
In order to determine the rate of litter decomposition of Fagus orientalis at two beech stands, litters from Vaz and Asalem with different parent material were collected in autumn. Litters of each region, put in four vases for 357 d in laboratory conditions. Sampling was taken within 21 d. The nitrogen, carbon and phosphorus were measured in each interval. On the first day, the amount of N was 0.73 % and 0.81 % and phosphorous was 817.5 mg/kg and 420 mg/kg in litter of Vaz and Asalem respectively. The amount of C was 43.4 % in Vaz and 41.6 % in Asalem. Rate of carbon variation showed no significant difference in two regions. Rate of nitrogen and phosphorus variation showed significant difference in two regions. C/N of litter reduced from 59.95 to 32.8 and from 47.7 to 28.7, C/P of litter reduced from 531 to 355 and from 989 to 479 in Vaz and Asalem, respectively.